Intramolecular Diels-Alder Reactions Utilizing Aldehyde and Ketone Dienophiles, A Rare Cycloaddition Reaction - T. Corcoran, James; Carberry, Patrick; R. Viernes, Dennis; D. Chisholm, John (Mini-Reviews in Organic Chemistry, 2015)
Intramolecular Diels-Alder reactions have become commonly employed transformations in the repertoire of the synthetic organic chemist. Variants of this reaction, which incorporate heteroatoms in the diene and dienophile, are also popular. Surprisingly, one of the least utilized intramolecular Diels-Alder cycloadditions utilizes a carbonyl (either an aldehyde or ketone) as a dienophile. While aldehyde dienophiles are routinely used in intermolecular Diels-Alder reactions, the intramolecular variant is significantly rarer. In this mini-review we will examine the known examples of intramolecular Diels-Alder reactions utilizing aldehyde or ketone dienophiles and evaluate the advantages and challenges associated with these reactions.
Keywords: Diels-Alder